PENERAPAN GREEN HUMAN RESOURCE MANAGEMENT DI UNIVERSITAS LANCANG KUNING - Mutiara Hati; Junaidi; Richa Afriana Munthe (Smart Education, 2026)
Abstrack: The global environmental crisis and the 2030 Agenda for Sustainable Development Goals (SDGs) position higher education institutions as strategic actors in promoting sustainability, including through environmentally oriented human resource management. This study examines the implementation of Green Human Resource Management (Green HRM) at Universitas Lancang Kuning (Unilak), a private university grounded in Malay cultural values that seeks to transform into a sustainable campus. The study aims to: (1) analyze the forms and level of Green HRM practices at Unilak, (2) identify supporting and inhibiting factors of its implementation, and (3) analyze the impact of Green HRM on campus environmental performance. A qualitative approach with an intrinsic case study design was employed, involving university leaders, HR managers, lecturers, and administrative staff selected through purposive sampling. Data were collected through in-depth interviews, observation, and document analysis, and were examined using thematic analysis. The findings indicate that Green HRM practices at Unilak have emerged through various green initiatives such as energy conservation, paper reduction, waste management, and the provision of green open spaces, yet remain at a medium level of institutionalization since they are not fully integrated into formal HR policies and performance management systems. Key supporting factors include top management commitment, alignment with the institutional vision, and the availability of several green facilities, while inhibiting factors comprise limited financial resources, the absence of standardized green performance indicators and reward schemes, and uneven ecological literacy among academic communities. Green HRM contributes to a cleaner and greener campus environment, increased pro-environmental work behaviors, and a stronger sustainability image for Unilak, but still requires a more structured strategic roadmap aligned with SDG targets 4.7 and 13.3. Keywords: Green Human Resource Management, Green Campus, AMO Theory, Sustainability, Universitas Lancang Kuning. Abstrak: Krisis lingkungan global dan tuntutan Agenda 2030 melalui Sustainable Development Goals (SDGs) menempatkan perguruan tinggi sebagai aktor strategis dalam mendorong pembangunan berkelanjutan, termasuk melalui pengelolaan sumber daya manusia yang berwawasan lingkungan. Penelitian ini mengkaji penerapan Green Human Resource Management (Green HRM) di Universitas Lancang Kuning (Unilak) sebagai perguruan tinggi swasta berbasis nilai budaya Melayu yang berupaya bertransformasi menuju kampus berkelanjutan. Tujuan penelitian adalah: (1) menganalisis bentuk dan tingkat penerapan praktik Green HRM di Unilak, (2) mengidentifikasi faktor-faktor pendukung dan penghambat implementasinya, serta (3) menganalisis dampak Green HRM terhadap kinerja lingkungan kampus. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus intrinsik, dengan subjek pimpinan universitas, pengelola SDM, dosen, dan tenaga kependidikan yang dipilih secara purposive. Data dikumpulkan melalui wawancara mendalam, observasi, dan studi dokumentasi, kemudian dianalisis secara tematik. Hasil penelitian menunjukkan bahwa praktik Green HRM di Unilak telah muncul dalam bentuk berbagai program hijau seperti penghematan energi, pengurangan penggunaan kertas, pengelolaan sampah dan ruang terbuka hijau, tetapi masih berada pada tingkat institusionalisasi menengah karena belum sepenuhnya terintegrasi dalam sistem kebijakan dan manajemen kinerja SDM. Faktor pendukung utama meliputi komitmen manajemen puncak, kesesuaian dengan visi institusi, serta ketersediaan sejumlah fasilitas hijau, sedangkan faktor penghambat mencakup keterbatasan anggaran, belum adanya indikator dan skema reward hijau yang baku, serta literasi ekologis sivitas akademika yang belum merata. Green HRM berkontribusi pada terciptanya lingkungan kampus yang lebih bersih dan asri, peningkatan perilaku kerja pro-lingkungan, serta penguatan citra keberlanjutan Unilak, namun masih memerlukan roadmap strategis yang lebih terstruktur dan selaras dengan target SDG 4.7 dan 13.3. Kata Kunci: Green Human Resource Management, Kampus Hijau, AMO Theory, Keberlanjutan, Universitas Lancang Kuning.